'Understanding' differs between English and German: Capturing systematic language differences of complex words. (July 2019) - Günther, Fritz; Smolka, Eva; Marelli, Marco
Abstract: In morphological processing, research has repeatedly found different priming effects by English and German native speakers in the overt priming paradigm. In English, priming effects were found for word pairs with a morphological and semantic relation ( SUCCESSFUL-success ), but not for pairs without a semantic relation ( SUCCESSOR-success ). By contrast, morphological priming effects in German occurred for pairs both with a semantic relation ( AUFSTEHEN-stehen, 'stand up'-'stand' ) and without ( VERSTEHEN-stehen, 'understand'-'stand' ). These behavioural differences have been taken to indicate differential language processing and memory representations in these languages. We examine whether these behavioural differences can be explained with differences in the language structure between English and German. To this end, we employed new developments in distributional semantics as a computational method to obtain both observed and compositional representations for transparent and opaque complex word meanings, that can in turn be used to quantify the degree of semantic predictability of the morphological system of a language. We compared the similarities between transparent and opaque words and their stems, and observed a difference between German and English, with German showing a higher morphological systematicity. The present results indicate that the investigated cross-linguistic effect can be attributed to quantitatively-characterized differences in the speakers' language experience, as approximated by linguistic corpora.